Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

Origin and global spread of an endemic chytrid fungus lineage linked to the bullfrog trade - Luisa P. Ribeiro; Julia R. Ernetti; Joice Ruggeri; Thomas S. Jenkinson; Adeline Loyau; Helen Butler; Tina Cheng; Dirk S. Schmeller; Timothy Y. James; Luís Felipe Toledo (Biological Conservation, 2026)

Conservation of an isolated and genetically unique population: red squirrels on the Isle of Wight - Alyson E.V. Buchanan; Demetra Andreou; Kathy H. Hodder; Melissa A. Toups; Phillipa K. Gillingham; Marin Cvitanović; Helen Butler; Emilie A. Hardouin (Biodiversity and Conservation, 2025)
Island populations face a higher extinction risk than mainland ones due to their smaller population sizes, limited genetic diversity, and increased vulnerability to environmental changes and stochastic events. The Isle of Wight red squirrel population is culturally and economically significant, being the largest remaining population in Southern England and genetically distinct from European populations. We used a multidisciplinary approach to assess the population’s long-term viability, evaluating habitat and food resources, analysing microsatellite genetic data, and using life history data to model population viability. Results indicated that natural food resources, supplemented by additional feeding, could sustain and support population growth. Microsatellite data identified two genetic clusters in the east and west of the island. Although F ST values were non-significant, indicating gene flow between subpopulations, elevated F IS values suggest localised mating dynamics driven by limited dispersal and spatial structure rather than systemic inbreeding. Population viability analyses suggested that habitat fragmentation and localised inbreeding do not pose immediate threats. However, maintaining connectivity between subpopulations remains crucial to preserving genetic diversity and reducing future risks of genetic isolation or increased inbreeding. Under pessimistic scenarios with reduced survival rates and fewer litters, model predictions indicated population decline and increased extinction risks. Future research should incorporate fine-scale spatial genetic analyses using genome data to explore population structure, local adaptation, and differentiate local mating dynamics from population-wide inbreeding. While direct data on inbreeding, litter sizes, and survival rates are challenging to obtain, these insights are critical for understanding population dynamics and guiding conservation efforts.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social group size influences pathogen transmission in salamanders - Kendra L. Ritchie; Vance T. Vredenburg; Shruti Chaukulkar; Helen M. Butler; Andrew G. Zink (Behavioral Ecology and Sociobiology, 2021)

Wildlife conservation in a fragmented landscape: the Eurasian red squirrel on the Isle of Wight - Emilie A. Hardouin; Helen Butler; Marin Cvitanović; Rainer G. Ulrich; Vanessa Schulze; Anna-Katarina Schilling; Peter W. W. Lurz; Anna Meredith; Kathy H. Hodder (Conservation Genetics, 2021)
Island populations may have a higher extinction risk due to reduced genetic diversity and need to be managed effectively in order to reduce the risk of biodiversity loss. The Eurasian red squirrels ( Sciurus vulgaris ) in the south of England only survive on three islands (the Isle of Wight, Brownsea and Furzey islands), with the Isle of Wight harbouring the largest population in the region. Fourteen microsatellites were used to determine the genetic structure of red squirrel populations on the Isle of Wight, as well as their relatedness to other populations of the species. Our results demonstrated that squirrels on these islands were less genetically diverse than those in Continental mainland populations, as would be expected. It also confirmed previous results from mitochondrial DNA which indicated that the squirrels on the Isle of Wight were relatively closely related to Brownsea island squirrels in the south of England. Importantly, our findings showed that genetic mixing between squirrels in the east and west of the Isle of Wight was very limited. Given the potential deleterious effects of small population size on genetic health, landscape management to encourage dispersal of squirrels between these populations should be a priority.

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Omnivory and predation impact of the calanoid copepod Boeckella poppei in a maritime Antarctic lake - Helen Butler; Angus Atkinson; Marina Gordon (Polar Biology, 2005)

The Use of Inverse Phase Gas Chromatography to Measure the Surface Energy of Crystalline, Amorphous, and Recently Milled Lactose - Helen E. Newell; Graham Buckton; David A. Butler; Frank Thielmann; Daryl R. Williams (Pharmaceutical Research, 2001)